My world history - Karpiel, Frank .; Krull, Kathleen; Wiggins, Grant (Boston, Mass. : Pearson, 2012)
Take your child on a journey through time without leaving home. With innovative resources, project-based activities, and unprecedented support for all learners, myWorld History takes students beyond the printed page to actively experience the history of the world in which they live.
Core concepts handbook -- Unit 1. Origins -- Unit 2. The ancient Near East -- Unit 3. Ancient India and China -- Unit 4. Ancient Greece -- Unit 5. Ancient Rome -- Unit 6. The Byzantine Empire and Islamic civilization -- Unit 7. African and Asian civilizations -- Unit 8. Civilizations of the Americas -- Unit 9. Europe in the Middle Ages -- Unit 10. The rise of Europe -- Unit 11. The early modern world -- Unit 12. The modern world.
At head of title: Pearson. Edition statement from publisher's website. Includes index. Except for the overview proguide, each of the teacher's proguides correlates to an individual unit in the student ed.
CAS
Keywords: History -- Study and teaching (Middle school).; History -- Textbooks; World history -- Textbooks; Social sciences -- Study and teaching (Middle school)